Addressing Violence against Women under COVID-19 in Brazil - Bastos, Gabriela; Carbonari, Flavia; Tavares, Paula (World Bank, Washington, DC, 2020)
This note aims at providing support to federal and subnational governments in understanding the increased risks of Violence against Women (VAW) in the country under Coronavirus (COVID-19) and providing the most appropriate responses in the short, medium and longer term. It points to evidence of epidemic-related risk factors connected to increased levels of VAW, trends of VAW during the Coronavirus (COVID-19) epidemic in Brazil, policy measures and interventions implemented globally to mitigate adverse impacts, as well as response efforts that have been put in place both by governments and civil society organizations. It also compiles existing data available on increased VAW in the country since the onset of the Coronavirus (COVID-19 pandemic, pointing to the main (direct and indirect) links between the two.